Elastin is a Key Regulator of Outward Remodeling in Arteriovenous Fistulas. Issue 4 (April 2015) - Wong, C.Y.; Rothuizen, T.C.; de Vries, M.R.; Rabelink, T.J.; Hamming, J.F.; van Zonneveld, A.J.; Quax, P.H.A.; Rotmans, J.I.
Abstract : Objectives: Maturation failure is the major limitation of arteriovenous fistulas (AVFs) as hemodialysis access conduits. Indeed, 30–50% of AVFs fail to mature due to intimal hyperplasia and insufficient outward remodeling. Elastin has emerged as an important determinant of vascular remodeling. Here the role of elastin in AVF remodeling in elastin haplodeficient (eln +/– ) mice undergoing AVF surgery has been studied. Methods: Unilateral AVFs between the branch of the jugular vein and carotid artery in an end to side manner were created in wild-type (WT) C57BL/6 ( n  = 11) and in eln +/– mice ( n  = 9). Animals were killed at day 21 and the AVFs were analyzed histologically and at an mRNA level using real-time quantitative polymerase chain reaction. Results: Before AVF surgery, a marked reduction in elastin density in the internal elastic lamina (IEL) of eln +/– mice was observed. AVF surgery resulted in fragmentation of the venous internal elastic lamina in both groups while the expression of the tropoelastin mRNA was 53% lower in the eln +/– mice than in WT mice ( p <  .001). At 21 days after AVF surgery, the circumference of the venous outflow tract of the AVF was 21% larger in the eln +/– mice than in the WT mice ( p  = .037), indicating enhanced outward remodeling in the eln +/– mice. No significant difference in intimal hyperplasia was observed. The venous lumen of the AVF in the eln +/– mice was 53% larger than in the WT mice, although this difference was not statistically significant (eln +/–, 350, 116 ± 45, 073 μm 2 ; WT, 229, 405 ± 40, 453 μm 2 ; p  = .064). Conclusions: In a murine model, elastin has an important role in vascular remodeling following AVF creation, in which a lower amount of elastin results in enhanced outward remodeling. Interventions targeting elastin degradation might be a viable option in order to improve AVF maturation.